2017
DOI: 10.1194/jlr.m079723
|View full text |Cite
|
Sign up to set email alerts
|

DGKζ deficiency protects against peripheral insulin resistance and improves energy metabolism

Abstract: Diacylglycerol kinases (DGKs) regulate the balance between diacylglycerol (DAG) and phosphatidic acid. DGKζ is highly abundant in skeletal muscle and induces fiber hypertrophy. We hypothesized that DGKζ influences functional and metabolic adaptations in skeletal muscle and whole-body fuel utilization. DAG content was increased in skeletal muscle and adipose tissue, but unaltered in liver of DGKζ KO mice. Linear growth, body weight, fat mass, and lean mass were reduced in DGKζ KO versus wild-type mice. Converse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Higher levels of expression of PEA15 have been reported in both patients with diabetes mellitus type 2 (Condorelli et al, 1998) and in euglycemic patients with impaired insulin sensitivity (Valentino et al, 2006). The DGKZ gene, already discussed above, has been proven to play a role in the protection against peripheral insulin resistance and in improving overall energy metabolism (Benziane et al, 2017). SLC2A1, also known as glucose transporter 1 (GLUT1), is the major glucose transporter in the human placenta and the ratelimiting step of glucose transport from the placenta to the fetus (Illsley, 2000).…”
Section: Energy Metabolism and Insulin Resistancementioning
confidence: 97%
See 1 more Smart Citation
“…Higher levels of expression of PEA15 have been reported in both patients with diabetes mellitus type 2 (Condorelli et al, 1998) and in euglycemic patients with impaired insulin sensitivity (Valentino et al, 2006). The DGKZ gene, already discussed above, has been proven to play a role in the protection against peripheral insulin resistance and in improving overall energy metabolism (Benziane et al, 2017). SLC2A1, also known as glucose transporter 1 (GLUT1), is the major glucose transporter in the human placenta and the ratelimiting step of glucose transport from the placenta to the fetus (Illsley, 2000).…”
Section: Energy Metabolism and Insulin Resistancementioning
confidence: 97%
“…Wang et al (Wang et al, 2013) and Yates et al (Yates et al, 2012) already reported that hypoxemia and hypoglycaemia undergone during IUGR decrease muscle mass in offspring. DGKZ (found hypomethylated, overexpressed) is known to induce muscle fiber hypertrophy and plays a role in the adaptation to energy metabolism alterations (Benziane et al, 2017). FOXK1 induces muscle progenitor cell proliferation and inhibits their differentiation (Shi et al, 2012).…”
Section: Heart and Skeletal Muscle Developmentmentioning
confidence: 99%
“…In contrast, whole-body deletion of DGKε triggers DAG accumulation in skeletal muscle but improves glucose tolerance [ 44 ]. Lastly, DGKζ KO mice exhibit improved muscle insulin sensitivity [ 45 ]. Altogether, these conflicting results might be explained by the specific subcellular DAG localizations and substrate preferences of the various enzyme isoforms and justify the need to further unravel the mechanisms through which DAGs drive IR.…”
Section: Causal Role Of Dags In Insulin Resistance?mentioning
confidence: 99%
“…In contrast to other DGK isoform-specific KO mouse models including DGK, DGK, and DGK (8,30,49), the metabolic phenotype of DGK KO mice is subtle. Several of the assays utilized in this study have also been applied to other DGK isoform-specific KO mouse models.…”
Section: Discussionmentioning
confidence: 82%